2018
DOI: 10.21702/rpj.2009.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of creative abilities on group's functional and role structure

Abstract: В статье приводятся результаты исследования воздействия творческих способностей на функционально-ролевую структуру группы и общегрупповые показатели творчества, дается качественный и количественный анализ полученных данных.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results obtained are consistent with the research of Dautov, D. F. (2009), aimed at studying the effectiveness of collaborative thinking activity in student groups that solve various types of problems. The research was based on theoretical ideas (Belousova, 2002) about the functions: generation, selection, meaning transfer, implementation, providing collaborative thinking activity.…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…The results obtained are consistent with the research of Dautov, D. F. (2009), aimed at studying the effectiveness of collaborative thinking activity in student groups that solve various types of problems. The research was based on theoretical ideas (Belousova, 2002) about the functions: generation, selection, meaning transfer, implementation, providing collaborative thinking activity.…”
Section: Tablesupporting
confidence: 88%
“…The research was based on theoretical ideas (Belousova, 2002) about the functions: generation, selection, meaning transfer, implementation, providing collaborative thinking activity. Dautov found that when problem solving is organized, when roles are distributed among students, there is a higher efficiency of collaborative thinking activity in student groups (Dautov, 2009). His research also highlighted certain personal characteristics of participants that affect the distribution of functions in collaborative thinking.…”
Section: Tablementioning
confidence: 97%